Construction of an Indian Literary Historiography through H.H. Wilson’s “Hindu Fiction” - Saklani, Astha (International Journal of English Literature and Social Sciences (IJELS), 2019)
Postcolonial scholars are largely in consensus that the modern Indian literary historiography is a gift of our colonial legacy. Most of these scholars have looked at the classical Sanskrit texts and their treatment by the Orientalists. One genre that is often ignored, however, by them, is that of fables. Fables formed a significant section of the Indian literature that was studied by the orientalists. The colonial intellectuals’s interest in selected Indian fables is reflected in H.H. Wilson’s essay entitled “Hindu Fiction”. The essay not only helps in deconstruting the motive behind British pre-occupation in the genre but also is significant in deconstructing the colonial prejudices which plagued the minds of the nineteenth century European scholars in general and colonial scholars in particular regarding the Asian and African communities and their literature.